EVALUATION OF CHANGES IN LABORATORY PARAMETERS IN PATIENTS AFTER KIDNEY TRANSPLANTATION FOLLOWING TREATMENT PROCEDURES (World Bulletin of Public Health, 2026)
The article presents a comparative study of laboratory parameters over time in patients who underwent kidney transplantation. It also demonstrates that fibroblast-23 has a strong correlation with phosphorus, calcium, vitamin D, and parathyroid hormone, and plays a central role in phosphate homeostasis in the body. These findings were confirmed by strong correlations observed in patients who underwent kidney transplantation